36 High prevalence of asymptomatic left ventricular dysfunction despite excellent risk factor control in a diabetic cohort. (7th October 2015) - James, S; Gallagher, J; Kenny, C; Waterhouse, D; McCambridge, J; Murphy, T; O'Connell, E; Ledwidge, M; Watson, C; Harkins, V; McDonald, K
Abstract : Introduction: Diabetes mellitus is an established cause of left ventricular dysfunction and a strong independent predictor of new onset heart failure. The STOP-HF Midlands project is a screening programme utilising NT-proBNP and collaborative care to detect left ventricular dysfunction in an asymptomatic diabetic cohort. Method: 612 diabetic patients attending the STOP-HF Midlands were included in this analysis. The demographic characteristics and biomarkers of traditional risk factor control in diabetics were recorded, including NT-proBNP. Doppler-echocardiography was performed if the NT-proBNP was >250 pg/mL. Left ventricular systolic dysfunction (LVSD) was defined as left ventricular ejection fraction of <50%. Left ventricular diastolic dysfunction (LVDD) was defined by left atrial volume index (LAVI) >34 ml/m 2 with lateral E´ <10 cm/s. Result: 152 (mean age 71.8 years; 57.9% male) of the diabetic cohort required echocardiography, with a median NT-proBNP of 419 pg/mL [252: 808]. Treated hypertension was present in 50% of the group with use of renin angiotensin aldosterone (RAAS) modifying therapies in 60.9%. The blood pressure in this cohort was 128 mmHg ±18 (SD) over 71 mmHg±11 (SD). The total cholesterol, HDL, LDL and triglyceride were 3.8 mmol/L ±0.9 (SD), 1.4 mmol/L ±1.3 (SD), 2.2 mmmol/L ±1.0 (SD), 1.6 mmol/L ±1.2 (SD) respectively. The creatinine was 95.2 μmol/L ±28.1 (SD) and HbA1c was 48.7 mmol/mol ±13.6 (SD). 5.3% of the cohort was found to have LVSD. 28.3% patients had LVDD. 31.3% had LVSD with or without LVDD of LAVI >34 ml/m 2 with lateral E <10 cm/s. Conclusion: These data demonstrate a high prevalence of significant asymptomatic left ventricular dysfunction in a community diabetic cohort despite excellent control of risk factors. Wider use of RAAS modifying therapy in this cohort might reduce the burden of this problem and slow the development to heart failure. The observations indicate that this population should be a focus of efforts to prevent heart failure.